SANDAK DALAM PERSPEKTIF HUKUM PERDATA NASIONAL - Endang Pristiwati (Syariah: Jurnal Hukum dan Pemikiran, 2014)
Sandak is lien land that constitutes sale transaction in culture law (not as assurance institution). However, sandak purchasers could not have sandak land because they have obligation to take back the land at redemption. So, it has not expiration date. In this transaction practice, it has a strong relationship with elements of extortion and it is really disserve the sandak seller. Because of that, it is need to further regulation. On Laws No. 56/PRP/1960, sandak is limited the time period. Beside in that rule, sandak becomes more similar with assurance institution. However, on supreme court decision in 1981 toward sandak land that has passed certain period is not taken back and there is no claim refund, then sandak purchaser can become a sandak owner. While until this time, society is seldom to know about the exist of that rule, so the extortion is continuos. Besides, the new law, Laws No. 4 year 1996 about dependent rights, is not arrange this sandak problem as well.